Rodovia BR-163: entre a geopolítica e a geoeconomia - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The geographic displacement of part of the Brazilian agricultural production, previously concentrated in the South and Southeast regions and, currently, with production concentrations in the Midwest and in the northern region of Brazil, resulted in the assembly and consolidation of a terrestrial circulation infrastructure to meet to an increasing demand for internal flows between producing regions and port complexes. In this context, the research sought to understand spatial arrangements and territorial transformations in a logistics corridor for the flow of commodities involving the BR-163 and a set of engineering systems that were and are being implanted along the rivers, with emphasis on the port areas in the municipality of Itaituba, Rurópolis, Santarém, Santana and Barcarena. In order to carry out the research, it was decided to make a historical and bibliographical survey of the process of construction of highway BR-163, the State's performance in the elaboration and execution of territorial policies; another part consisted in reading the classics of circulation, transport and logistics, including also the classical geography and geopolitics and geoeconomics; it was sought to carry out interviews in the field work, with some actors involved, ranging from the social movements to the companies that operate the port infrastructures. The consolidation of another export corridor of agricultural commodities towards the northern region of Brazil substantially altered the regional circulation with the insertion of new engineering systems and new river routes along the rivers, and a convergence of road flows to the municipality of Itaituba, which became the point of concentration of international and national investments in transport infrastructure that support the flows, and this municipality now has the largest number of cargo transhipment ports and an articulated set of infrastructures that make it possible to circulation.
Keywords: Rodovia BR-163; Geopolítica; Geoeconomia; Amazônia; CIÊNCIAS HUMANAS: GEOGRAFIA